HIV-1 Transmission linkages among persons with incident infection to inform public health surveillance. (July 2021) - Dennis, Ann M.; Frost, Simon D.W.; Enders, Kimberly; Cressman, Andrew E.; Volz, Erik; Adams, Nicole; Miller, William C.; Cohen, Myron S.; Mobley, Victoria; Samoff, Erika; Eron, Joseph J.
Abstract: Background: We evaluated features of HIV transmission networks involving persons diagnosed during incident HIV infection (IHI) to assess network-based opportunities to curtail onward transmission. Methods: Transmission networks were constructed using partial pol sequences reported to North Carolina surveillance among persons with recent (2014–2018) and past (<2014) HIV diagnoses. IHI were defined as documented acute infections or seroconversion. Demographic and virologic features of HIV genetic clusters (<1.5% pairwise genetic distance) involving ≥ 1 IHI were assessed. Persons with viral genetic links and who had diagnoses >90 days prior to an IHI were further characterized. We assessed named partner outcomes among IHI index persons using contact tracing data. Findings: Of 4, 405 HIV diagnoses 2014–2018 with sequences, there were 323 (7%) IHI index persons; most were male (88%), Black (65%), young (68% <30 years), and reported sex with men (MSM) risk (79%). Index persons were more likely to be cluster members compared to non-index persons diagnosed during the same period (72% vs. 49%) . In total, 162 clusters were identified involving 233 IHI, 577 recent diagnoses, and 163 past diagnoses. Most IHI cases (53%) had viral linkages to ≥1 previously diagnosed person without evidence of HIV viral suppression in the year prior to the diagnosis of the IHI index. In contact tracing, only 53% IHI cases named an HIV-positive contact, resulting in 0.5 previously diagnosed persons detected per IHI investigated. When combined with viral analyses, the detection rate of viremic previously diagnosed persons increased to 1.3. Interpretation: Integrating public health with molecular epidemiology, revealed that more than half of IHI have viral links to persons with previously diagnosed unsuppressed HIV infection which was largely unrecognized by traditional contact tracing. Enhanced partner services to support engagement and retention in HIV care and improved case finding supported by rapid phylogenetic analysis are tools to substantially reduce onward HIV transmission. Funding: The project described was supported by the National Institute of Allergy and Infectious Diseases (NIAID), NIH, through Grant Award Number R01AI135970.